INSULIN THERAPY IN T2DM PATIENTS IN DIABETES OUTPATIENT CLINIC, DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA - Sri Murtini; Sidarti Soehita; Adinda Ayu Dyah Rahadini (Universitas Airlangga, Surabaya, Indonesia, 2023)
Highlights1. The occurrence of macrovascular and microvascular problems is strongly associated with high mortality in type 2 diabetes mellitus (T2DM).2. Combinations of rapid-acting and long-acting insulin were the most frequent kind of insulin. AbstractBackground: High mortality in type 2 diabetes mellitus (T2DM) has a strong correlation with the presence of macrovascular and microvascular complications. The risk of these complications can be reduced through good glycemic control. As the disease progresses, patients may need to add or switch to insulin therapy rather than oral antihyperglycemic drugs to achieve desirable glycemic control. Objective: To determine the pattern of insulin therapy and glycemic control in T2DM patients. Material and Method: Data for this study were obtained from the medical records of the Diabetes Outpatient Clinic at the Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. This study was an observational descriptive. In June-July 2016, total samples were collected from 124 patients who received insulin therapy between February 2015 and March 2015. Result: According to the data obtained, the most commonly used insulin was a combination of rapid-acting and long-acting insulin (75.8%). While basal bolus insulin (75.8%) accounts for the most common regimen used to administer insulin, only 27.4% and 45% of total patients achieved good glycemic control based on FPG and PPG testing, respectively. HbA1c testing was done on 44 out of 124 people, with 9 people (20.5%) met the target of HbA1c <7%. Conclusion: Glycemic control in T2DM patients who received insulin therapy was relatively low.